JNJ-64619178 radiosensitizes and suppresses fractionated ionizing radiation-induced neuroendocrine differentiation (NED) in prostate cancer - Pawar, Jogendra Singh; Al-Amin, Md. Yusuf; Hu, Chang-Deng (Frontiers in Oncology, 2023)
Background: Radiation therapy (RT) is a standard treatment regimen for locally advanced prostate cancer; however, its failure results in tumor recurrence, metastasis, and cancer-related death. The recurrence of cancer after radiotherapy is one of the major challenges in prostate cancer treatment. Despite overall cure rate of 93.3% initially, prostate cancer relapse in 20-30 % patients after radiation therapy. Cancer cells acquire radioresistance upon fractionated ionizing radiation (FIR) treatment, eventually undergo neuroendocrine differentiation (NED) and transform into neuroendocrine-like cells, a mechanism involved in acquiring resistance to radiation therapy. Radiosensitizers are agents that inhibit the repair of radiation-induced DNA damage. Protein arginine methyltransferase 5 (PRMT5) gets upregulated upon ionizing radiation treatment and epigenetically activates DNA damage repair genes in prostate cancer cells. In this study, we targeted PRMT5 with JNJ-64619178 and assessed its effect on DNA damage repair gene activation, radiosensitization, and FIR-induced NED in prostate cancer. Methods: γH2AX foci analysis was performed to evaluate the DNA damage repair after radiation therapy. RT-qPCR and western blot were carried out to analyze the expression of DNA damage repair genes. Clonogenic assay was conducted to find out the surviving fraction after radiation therapy. NED was targeted with JNJ-64619178 in androgen receptor (AR) positive and negative prostate cancer cells undergoing FIR treatment. Results: JNJ-64619178 inhibits DNA damage repair in prostate cancer cells independent of their AR status. JNJ-64619178 impairs the repair of ionizing radiation-induced damaged DNA by transcriptionally inhibiting the DNA damage repair gene expression and radiosensitizes prostate, glioblastoma and lung cancer cell line. It targets NED induced by FIR in prostate cancer cells. Conclusion: JNJ-64619178 can radiosensitize and suppress NED induced by FIR in prostate cancer cells and can be a potential radiosensitizer for prostate cancer treatment.